World Military Expenditures and Arms Transfers, 1967-1976 ([Verlag nicht ermittelbar], 1984)
This data collection contains two files of world military expenditures and arms trade data for 145 countries in the period 1967-1976. Part 1 data consist of a yearly series of data for population and national military expenditures, including the value of weapons exports and imports. The country and the year form the unit of analysis, so that each country appears ten times, once for each year. Data are provided in millions of United States current and constant dollars for the total arms imports and exports, as well as for the total imports and exports of goods and services. Various socioeconomic data are presented to provide a comparative background for the series. Data are provided in millions of United States current and constant dollars for the gross national product (GNP), and for military expenditures, central government expenditures, public health expenditures, and public education expenditures as a percentage of the gross national product. Additional variables provide information on the number of armed forces personnel, teachers, and physicians per 1,000 people. Part 2 data consist of information on the total transactions in the transfer of armaments. Data are provided for the total value of arms imported by each country from individual major arms suppliers, which include the United States, United Kingdom, France, Canada, China, Poland, West Germany, and Czechoslovakia.